Perbedaan ketersediaan makanan dan lingkungan rumah pada anak obesitas dan tidak obesitas - A Fahmy Arif Tsani; Fillah Fithra Dieny; Zahra Anggita Pratiwi (AcTion: Aceh Nutrition Journal, 2022)
Obesity incidence in children, especially primary school children, is increasing. This obesity can be caused by environmental factors: availability of food at home and the home environment or home environment such as the physical environment, exposure to screen time, mother knowledge, and maternal behaviour in providing feeding practices. This study aims to determine the difference between food availability and home environment for obese and non-obese children. The design of this research was case-control conducted with the subject of elementary school-age children in Yogyakarta city. The research was conducted in March-November 2017. Samples were chosen by the multistage sampling method. Subjects were grouped into children with obese nutritional status as a case (n=71) and children with normal nutritional status as control (n=71) based on the BFA index. The data were collected by anthropometric measurements, interviewing, and filling out Home Environment Survey questionnaires on children and their parents. Data analysis using Mann Whitney statistical test, Spearman test, McNemar test, and logistic regression. Food availability showed significant mean differences in case and control groups (p <0,05). Other environmental factors showed no significant differences, but in the case group, the mother's feeding scores were less healthy than the control group; the average duration of case group screen time was higher than 20 minutes than the control group; higher physical environmental support scores control group than case groups. In conclusion, food availability had significant mean differences in both groups.